Assuring culture fairness in social studies testing at the basic level of education in Nigeria (2012)
The paper examined the need to ensure culture fairness in social studies testing in Nigeria schools in view of the introduction of new concepts into the curriculum. The meaning of the main concepts that underpin the discourse of the paper-culture and culture fairness were discussed bringing out their relevance in achieving fairness in social studies testing. Principles and procedures that can guide social studies teachers in ensuring culture-fairness in testing were highlighted.